Signsync / Muhammad Haris Irfan Azahari … [et al.] - Azahari, Muhammad Haris Irfan; Abd Hamid, Nadim; Noor Azman, Noor Aqilah; Hazwani, Nurul Batrisyia; Baharom, Siti Nurhafizah; Mohd Shah, Radziatul Shima (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The sign language glove is a revolutionary invention that aims to bridge the communication gap between the mute community and individuals who do not understand sign language. This wireless glove, called SignSync, converts sign language into spoken words, making it easier for people to communicate with each other. The use of a wireless battery in the glove adds convenience and portability, allowing users to wear it comfortably and use it anywhere. The idea of a sign language glove is not entirely new, as inventor Roy Allela created a similar device called Sign-IO Gloves in 2019. However, SignSync aims to improve upon this design by combining all the necessary devices and functions into one, making it simpler and more user-friendly. This innovation eliminates the need for multiple devices and reduces the burden on users. The sign language glove has practicality and usefulness in providing communication access and fostering inclusivity and understanding. Its wireless design allows for easy transportation, and its affordability enhances its market potential. The potential for commercialization is high, given the increasing demand for inclusive technology. Overall, the sign language glove represents a significant step towards creating a more inclusive and communicative society.